Peran Amanat Agung Terhadap Penyembah Watu Pinawetengan - Taogan, Frischo Ridhoi; Suseno, Aji; Arifianto, Yonatan Alex (Pusat Studi Pentakosta Indonesia, 2022)
Minahasa is one of the ethnic groups in North Sulawesi. Christians are the majority in the area. Along with the development of Christianity in Minahasa, it did not make the indigenous religious culture erased. One of the concerns is the ritual carried out at Watu Pinawetengan called